Robert Kirk’s Attempted Intellectual Filicide: Are Phenomenal Zombies Hurt? - Sepetyi, D. P.; Сепетий, Дмитро Петрович (My University, 2022)
Abstract: In the paper, I discuss Robert Kirk’s attempt to refute the zombie argument against materialism by demonstrating, “in a way that is intuitively appealing as well as cogent”, that the idea of phe-nomenal zombies involves incoherence. Kirk’s argues that if one ad-mits that a world of zombies z is conceivable, one should also admit the conceivability of a certain transformation from such a world to a world z* that satisfies a description D, and it is arguable that D is incoherent. From which, Kirk suggests, it follows that the idea of zombies is incoherent. I argue that Kirk’s argument has several minor deficiencies and two major flaws. First, he takes for granted that cognitive mental states are physical (cognitive physicalism), although a zombist is free to—and would better—reject this view. Second, he confuses elements of different scenarios of transformation, none of which results in the incoherent description D.
https://orcid.org/0000-0003-2110-3044
Keywords: consciousness; conceivability; incoherence; materialism; phenomenal zombie; possibility